THE USE OF BLINDFOLD GAME TO IMPROVE THE VOCABULARY MASTERY OF THE FIFTH GRADE STUDENTS AT SDN TERTEK TULUNGAGUNG - Yanuri Yanuri (STKIP PGRI TULUNGAGUNG, 2015)
The researcher chose fifth grade students of SDN TERTEK as subject of the research, because the researcher teaches English in this school. The researcher found that the students have lack motivation in learning english. In this study the researcher chose Blindfold Game strategy to solve the problem she found. Based on the background of the research, the research problem is, “How can Blindfold Game be used to improve the fifth grade students’ vocabulary mastery at SDN TERTEK? The objective of the study was to improve the fifth grade students’ vocabulary mastery at SDN TERTEK, through Blindfold Game in teaching of vocabulary.The research design of the study was classroom action research. In this research, there were four phases, planning, acting, observing and reflecting. This research will be conducted by some cycles. The researcher investigated the fifth grade students vocabulary mastery of SDN TERTEK which was started in January and ended in February 2016.In this vocabulary pre test, the students were joined in the classroom there were 12 students failed the test and 8 students passed the test. In the Cycle I the researcher also gives post test, and there were 7 students got less score than criteria of success, and 13 students passed. It means that this cycle were unsuccessful, because the target of the criteria of success were 85%. So the researcher continued in the next cycle. In the cycle II the researcher changed strategy, the strategy was ask the students to practice in front of class. The result of post test in the cycle II there were 2 students who failed and 18 students passed. The students were more interesting with the lesson and they could improve their vocabulary mastery.Based on the result of the study showed that the students’ vocabulary mastery was increased. To english teacher it is expected to motivate the English teacherto apply a useful teaching technique to improve the students’ vocabulary. For the other teacher, the researcher suggest them to be useful as a references before making a research dealing with implementation of Blindfold Game Technique in improving students’ vocabulary mastery.